2015
DOI: 10.1016/j.biocel.2015.07.006
|View full text |Cite
|
Sign up to set email alerts
|

JMJD3 as an epigenetic regulator in development and disease

Abstract: Gene expression is epigenetically regulated through DNA methylation and covalent chromatin modifications, such as acetylation, phosphorylation, ubiquitination, sumoylation, and methylation of histones. Histone methylation state is dynamically regulated by different groups of histone methyltransferases and demethylases. The trimethylation of histone 3 (H3K4) at lysine 4 is usually associated with the activation of gene expression, whereas trimethylation of histone 3 at lysine 27 (H3K27) is associated with the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
96
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(101 citation statements)
references
References 98 publications
(146 reference statements)
5
96
0
Order By: Relevance
“…This gene is essential for life after birth, as knockout mice are born smaller and die perinatally due to respiratory failure (21,61,62). Previous studies have pointed to a potential tumor-suppressive role of KDM6B in specific tissues (such as lung, colon, and pancreas) (30)(31)(32)63), while in others (such as blood, breast, and brain) it may play an opposite tumor-promoting function (24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This gene is essential for life after birth, as knockout mice are born smaller and die perinatally due to respiratory failure (21,61,62). Previous studies have pointed to a potential tumor-suppressive role of KDM6B in specific tissues (such as lung, colon, and pancreas) (30)(31)(32)63), while in others (such as blood, breast, and brain) it may play an opposite tumor-promoting function (24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…Targeting epigenetic regulators is emerging as promising cancer therapy. Pharmacological inhibitors of KDM6B (such as GSK-J4) (75) were shown to inhibit growth of different cancer cell lines, such as T-ALL and glioma (20,21,76,77), in which KDM6B plays an oncogenic role (22). While use of these compounds would obviously be contraindicated for squamous cancer, other drugs enhancing KDM6B function or inhibiting epigenetic modifying enzymes with an opposite role could be of benefit and open novel windows of opportunity for both prevention and treatment of this disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trimethylation of H3K37 is typically associated with gene inactivation, while monomethylation of H3K27 is associated with gene activation 18 19 . Kdm6b is reported to be involved in many cellular processes, such as proliferation, differentiation, apoptosis and senescence 20. Homozygous Kdm6b -deficient newborn mice were reported to become cyanotic within minutes due to respiratory failure and died shortly with kyphosis and severe lordosis 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Our laboratory has previously observed that SFB colonization can increase serum levels of SAA (11), but this had not been explored beyond acute colonization with the bacteria. During acute colonization with SFB, serum levels of the DAMP SAA were significantly increased, as was bone marrow expression of Jmjd3, encoding an H3K27 demethylase (36). However, SAA and Jmjd3 did not remain elevated after SFB was cleared.…”
Section: Discussionmentioning
confidence: 96%